Is it possible to detect fire history by dating charcoal in humus? - Rosengren, Mats (2005)
This study estimates the total amount of charcoal/ha and examines the possibility of detecting fire history by radiocarbon dating charcoal in humus from three stands in northern Sweden; one Pinus-Cladina, one Pinus-Vaccinium and one Picea-herb stand. All stands have the same fire history documented by dendrochronology. Samples of brushwood charcoal were taken in the uppermost and lowermost part of the charcoal layers, and radiocarbon dated with Accelerator Mass Specthrometry (AMS). The results show that the Pinus-Vaccinium stand has the largest charcoal record, c. 5400 kg/ha, and the Pinus-Cladina stand the smallest, c. 850 kg/ha. The charcoal samples are too young (≤600 years) to give accurate dating results for a comparison with the documented fires dated by dendrochronology. It is concluded that the persistence of charcoal in humus is low and that wildfire is the most likely agent of charcoal degradation. Further, it is suggested that the two Pinus stands, having the youngest charcoal, are characterized by severe fires consuming old charcoal, while the fires in the Picea-herb stand generally are less severe, making it possible for old charcoal to accumulate. Therefore, the possibility of detecting fire history by radiocarbon dating charcoal in humus is probably restricted to stands where fire severity is lower or similar to the Picea-herb stand.